Permission to ponder : contemplative wisdom for the spiritually distracted - Balzer, Tracy, 1961- (Leafwood Publishers, an imprint of Abilene Christian University Press, 2015)
God gives us permission to meditatively ponder, even in the midst of our fragmented existence. He invites us to 'listen, that you may live.' Many Christians are distracted and dissatisfied. The external demands of life grip us, while our inner walk with God becomes ever more superficial and thin. Is there hope for authentic connection with God in a world of distractions, or must we be resigned to a spiritually shallow existence? Reflection, contemplation, and meditation are ancient practices that are losing ground in a highly technological world. Permission to Ponder examines the ways others have accepted the invitation from God to dwell deeply, beginning with 'the Four Marys' of the Gospels. In the midst of their stories, the classical discipline of lectio divina—praying the Scripture—will serve as a template for praying and pondering all of life.